Limitations of NIR Spectrometry as an Identification Test for Active Ingredients in Medicinal Products - N. E. Kuz'mina; S. V. Moiseev; B. K. Romanov (Регуляторные исследования и экспертиза лекарственных средств, 2021)
Near-infrared spectrometry (NIRS) is a new pharmacopoeial method. It is widely used in the pharmaceutical industry for quality control of medicinal products at various production stages (control of raw materials and finished products), and for detection of substandard and counterfeit drugs.The aim of the study was to assess the feasibility of using NIRS as an identification test for active ingredients during pre-marketing quality control of medicinal products.Materials and methods: 327 drugs samples represented as solid and semisolid dosage forms were tested by NIRS following their examination by well-established pharmacopoeial Identification methods during pre-marketing laboratory evaluation. The NIR spectra of the test samples were compared with the spectral library classification models.Results: NIRS confirmed the identity of 3.1% of the tested medicinal products. It was demonstrated that library classification models could be used for identification of only those medicines that were produced by a specific manufacturer, i.e. for confirmation of medicine identity.Conclusions: the NIRS method is unpractical as an Identification test for active ingredients in medicinal products during the pre-marketing laboratory evaluation stage. The main limitations of NIRS are lack of complete sets of library classification models for all medicinal products available in the market and non-reproducibility of spectral library data obtained with a different instrument.